Discovery of a new species and key to all known species of the genus Aalatettix Zheng & Mao (Orthoptera, Tetrigoidea, Tetrigidae) from China - Cao, Cheng-Quan; Shi, Jian-Ping; Yin, Zhan (Zootaxa, 2016)
The genus Aalatettix Zheng & Mao, 2002 (Orthoptera, Tetrigoidea, Tetrigidae) contains 9 valid species in China (Zheng & Mao, 2002; Zheng, Cao & Chen, 2011; Zheng, Lin & Zhang, 2013; Zheng, 2014a; Zheng, 2014b; Zheng & Lin, 2015; Zheng, Shi & Yin, 2015). During the identification of pygmy grasshopper specimens collected from Taiwan, China in 1998, a new species of the genus Aalatettix Zheng & Mao, 2002 was found and described below. A key to all known species of the genus is given in this paper. The type specimens are deposited in the National Museum of Natural Science, Taichung, Taiwan, China.